Propranolol plasma monitoring in children submitted to surgery of tetralogy of Fallot by a micromethod using high performance liquid chromatography (Clinics, 2007)
OBJECTIVE: To evaluate the analytical micromethod using liquid chromatography for the quantification of propranolol in children submitted to surgery of tetralogy of Fallot (TLF). Methods: Only 0.2 mL of plasma is required for the assay. Peaks eluted at 8.4 (Propranolol) and 17.5 min (verapamil, internal standard) from a C18 column, with a mobile phase 0.1 M acetate buffer, pH 5.0, and acetonitrile (60:40, v/v) at flow rate 0.7 mL/min, detected at 290 nm (excitation) and 358 nm (emission). Surgery was started 776 min of drug administration (8.7mg, mean); seven blood samples were collected from six patients (4M/2F; 2.1yrs;11.5kg; 0.80m; 18.9kg/m²). RESULTS: Confidence limits of the method showed high selectivity and recovery, sensitivity of 0.02ng/mL, good linearity (0.05-1000ng/mL), precision of 8.6% and accuracy of 3.1%. The mean duration of surgery was 283.2min, with the patients remaining under cardiopulmonary bypass (CPB) for 114min. A declining curve of propranolol plasma concentration was obtained after the last dose in the night that preceded the day of surgery. Plasma concentration also was normalized with hematocrit due to the hemodilution caused by the CPB procedure. On the other hand a decrease on drug plasma concentration was obtained between periods, the beginning of surgery to the postoperative day 2 (7.09 ng/mL and 0.05 ng/mL, p